Resilience in The Ruins - Sarasi, Vita; Nugraha, Denny Sidharta; Farras, Joval Ifghaniyafi; Fadillah, Afrizal; Aulia, Sulthonul; Setiono, Muhammad Fahri (Jurnal ICMES, 2024)
Amid the devastation caused by the Israeli occupation, the Palestinian economy faces profound systemic challenges, including trade restrictions, widespread unemployment, and collapsing infrastructure. This study adopts a systems thinking approach to explore economic survival under such conditions, bridging the gap in understanding the interconnected dynamics of macroeconomic and microeconomic factors. Using causal loop diagrams, the analysis uncovers reinforcing loops of poverty, aid dependency, and infrastructure collapse alongside balancing loops driven by community resilience and policy interventions. Key findings reveal that trade restrictions have caused GDP contractions of up to 35 percent, while unemployment in Gaza has surged to 45 percent due to disrupted labor markets. Furthermore, only 33 percent of hospitals remain operational, exacerbating health crises and food insecurity. The study emphasizes the critical need for targeted infrastructure investments to restore market functionality and reduce unemployment by 15–20 percent, paired with community empowerment to strengthen resilience. The systems thinking framework offers policymakers actionable insights to navigate the socio-economic complexities of occupation and promote sustainable survival strategies for Palestine.